CIVIC CHARACTER SOCIAL RELATIONS TOWARDS A STRONG NATIONAL UNITY BASED ON BROTHERHOOD - Akhyar, Zainul; Elmy, Muhammad; Kiptiah, Mariatul; Huda, Nurul; Hiliadi, Wardiani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
Social relations between citizens need to be developed to the level of